Engineering and Dissecting the Glycosylation Pathway of a Streptococcal Serine-rich Repeat Adhesin - Zhu, Fan (J Biol Chem, 2016)
Serine-rich repeat glycoproteins (SRRPs) are conserved in Gram-positive bacteria. They are crucial for modulating biofilm formation and bacterial-host interactions. Glycosylation of SRRPs plays a pivotal role in the process; thus understanding the glycosyltransferases involved is key to identifying new therapeutic drug targets. The glycosylation of Fap1, an SRRP of Streptococcus parasanguinis, is mediated by a gene cluster consisting of six genes: gtf1, gtf2, gly, gtf3, dGT1, and galT2. Mature Fap1 glycan possesses the sequence of Rha1–3Glc1-(Glc1–3GlcNAc1)-2,6-Glc1–6GlcNAc. Gtf12, Gtf3, and dGT1 are responsible for the first four steps of the Fap1 glycosylation, catalyzing the transfer of GlcNAc, Glc, Glc, and GlcNAc residues to the protein backbone sequentially. The role of GalT2 and Gly in the Fap1 glycosylation is unknown. In the present study, we synthesized the fully modified Fap1 glycan in Escherichia coli by incorporating all six genes from the cluster. This study represents the first reconstitution of an exogenous stepwise O-glycosylation synthetic pathway in E. coli. In addition, we have determined that GalT2 mediates the fifth step of the Fap1 glycosylation by adding a rhamnose residue, and Gly mediates the final glycosylation step by transferring glucosyl residues. Furthermore, inactivation of each glycosyltransferase gene resulted in differentially impaired biofilms of S. parasanguinis, demonstrating the importance of Fap1 glycosylation in the biofilm formation. The Fap1 glycosylation system offers an excellent model to engineer glycans using different permutations of glycosyltransferases and to investigate biosynthetic pathways of SRRPs because SRRP genetic loci are highly conserved.